1999
DOI: 10.1046/j.1469-8137.1999.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural 13C and 15N abundance of field‐collected fungi and their ecological implications

Abstract: The natural abundance of "$C and "&N was measured in basidiocarps of at least 115 species in 88 genera of ectomycorrhizal, wood-decomposing and litter-decomposing fungi from Japan and Malaysia. The natural abundance of "$C and "&N was also measured in leaves, litter, soil and wood from three different sites. "&N and "$C were enriched in ectomycorrhizal and wood-decomposing fungi, respectively, relative to their substrates. Ectomycorrhizal and wood-decomposing fungi could be distinguished on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
188
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(219 citation statements)
references
References 13 publications
(7 reference statements)
28
188
3
Order By: Relevance
“…As reported by several authors (Gebauer and Taylor, 1999;Henn and Chapela, 2001;Hobbie et al, 1999Hobbie et al, , 2001Högberg, 1997;Kohzu et al, 1999;Taylor et al, 2003, Trudell et al, 2004Zeller et al, 2007), δ 13 C values differed between sporophores of saprotrophic and ectomycorrhizal fungi. Sporophores of the two saprotrophic fungi from the Châteauvert site showed a 13 C enrichment compared to their substrates.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As reported by several authors (Gebauer and Taylor, 1999;Henn and Chapela, 2001;Hobbie et al, 1999Hobbie et al, , 2001Högberg, 1997;Kohzu et al, 1999;Taylor et al, 2003, Trudell et al, 2004Zeller et al, 2007), δ 13 C values differed between sporophores of saprotrophic and ectomycorrhizal fungi. Sporophores of the two saprotrophic fungi from the Châteauvert site showed a 13 C enrichment compared to their substrates.…”
Section: Discussionsupporting
confidence: 67%
“…Fungal sheaths were 2.4 to 6.4% enriched compared to the root core. Other studies have confirmed that sporophores of ectomycorrhizal fungi are often more enriched in 15 N than sporophores of saprotrophic fungi, whereas sporophores of saprotrophic fungi are almost always enriched in 13 C compared to sporophores of ectomycorrhizal fungi (Hobbie et al, 1999;2002;Kohzu et al, 1999;2000;Taylor et al, 2003;Trudell et al, 2004). Lilleskov et al (2002) demonstrated that isotope signatures reflect ecophysiological functions.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…As in the present study, Tricholoma and Cortinarius had significantly higher δ 15 N than Lactarius, Laccaria and Russula (P < 0.05 for each comparison). By contrast, Kohzu et al (1999) found no taxonomic patterns of N isotopic signature. However, they compared taxa at the family rather than genus level, and compared fungi from different sites, both of which could obscure taxonomic patterns.…”
Section: Nitrogen Isotopes and Protein Usementioning
confidence: 79%
“…Russula ). EMF taxa differ in their N isotopic signatures (Taylor et al , 1997;Gebauer & Taylor, 1999;Hobbie et al , 1999;Kohzu et al , 1999). Nitrogen isotopes may provide an independent line of evidence regarding N-use patterns if the combination of soil N pool signatures and physiological mechanisms of isotopic alteration during uptake, transformations, transfers and losses lead to a consistent isotopic distinction among physiological classes of fungi.…”
Section: Introductionmentioning
confidence: 99%